2021
DOI: 10.21608/jabps.2021.93867.1138
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in sepsis: friend or enemy?

Abstract: Infectious diseases are a major cause of death worldwide. A serious complication of infections is septic shock. Septic shock is a critical syndrome associated with the host response to infection. The severity of infections is related to an activation cascade that results in a magnification of the cytokine production which is termed "cytokine storm". Despite the commonly elucidated etiology of sepsis and its clinical course, the actual progress in therapeutic strategies is still limited. Several studies were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 152 publications
(162 reference statements)
0
1
0
Order By: Relevance
“…TNF-α is a major pro-inflammatory molecule first identified in 1975 and known to exert inflammatory effects. TNF-α is often the main target in the treatment of various inflammatory diseases and plays a role in infectious disease and sepsis pathophysiology [ 56 , 57 ]. In this study, we found a significant decrease in the serum TNF-α level in the septic rat group after MSC secretome administration at a dose of 150 µL and 300 µL compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a major pro-inflammatory molecule first identified in 1975 and known to exert inflammatory effects. TNF-α is often the main target in the treatment of various inflammatory diseases and plays a role in infectious disease and sepsis pathophysiology [ 56 , 57 ]. In this study, we found a significant decrease in the serum TNF-α level in the septic rat group after MSC secretome administration at a dose of 150 µL and 300 µL compared to the control group.…”
Section: Discussionmentioning
confidence: 99%